Sufi Shrine as Space of Hegemonic Struggle in Pakistan: An Ethnographic Account - Zahra, Seemab; Bilal, Muhammad; Azam, Shafia (Religions of South Asia, 2021)
In the post-9/11 period, while the rise of the Taliban and their alliance with Al-Qaeda accelerated radicalism in Pakistan, Sufism and Sufi shrines have been awarded the status of an antidote to counter the extremist propensities of orthodox Islam typically associated with mosques and madrasas. Nevertheless, contrary to popular belief, sectarian schism, loathing and violence have also been witnessed at several Sufi shrines across Pakistan. The article explores the dynamics of power struggle at the shrine of Bari Imam in Islamabad, Pakistan, while examining the role of sectarian conflicts and violence in achieving the desire for social and economic hegemony. Ethnographic research design was employed, involving participant observation while partaking in different activities of the shrine. Also, respondents including members of the Auqaf Department, pilgrims, caretaker(s) of the Bari Imam shrine and inhabitants of the area were interviewed. The respondents include both males and females of diverse age groups belonging to various socio-economic statuses, sectarian affiliation and educational backgrounds. The findings propose that regardless of the spiritual character of the Bari Imam shrine, it has become a pivot of economic and political power struggle, eventually engendering and escalating sectarian discord, violence and detestation.